2009
DOI: 10.1002/jrs.2187
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of micron‐sized hollow copper spheres with ZSM‐5 molecular sieve as a template

Abstract: A new, well-designed type of micron-sized hollow copper spheres was synthesized in this article. The process was performed using ZSM-5 molecular sieve as a template. It has the prominent advantage in that the various stages of pretreatment for the core material can be omitted because of the inherent nature of the ZSM-5 molecular sieve. The surface of the sieve consists entirely of negatively charged oxygen sites such that free Cu 2+ ions can easily be adsorbed and reduced there, acting thereafter as a seed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The micron-sized hollow copper spheres were prepared referencing our previous work [8]. Initially, 70 mg of ZSM-5 molecular sieve was poured, under continuous mechanical agitation, into 10 mL of an aqueous solution containing 120 mg of sodium hydroxide, 660 mg of EDTA, and 420 mg of copper sulfate pentahydrate, and the mixture was left for 5 min to form a suspension.…”
Section: Preparation Of Hollow Copper Spheresmentioning
confidence: 99%
See 1 more Smart Citation
“…The micron-sized hollow copper spheres were prepared referencing our previous work [8]. Initially, 70 mg of ZSM-5 molecular sieve was poured, under continuous mechanical agitation, into 10 mL of an aqueous solution containing 120 mg of sodium hydroxide, 660 mg of EDTA, and 420 mg of copper sulfate pentahydrate, and the mixture was left for 5 min to form a suspension.…”
Section: Preparation Of Hollow Copper Spheresmentioning
confidence: 99%
“…However, in contrast to the successful syntheses of polymer, oxide, and semiconductor products, developing a template-based synthesis of hollow metal spheres remains a great challenge, possibly because of the difficulty of removing the templates without breaking the shells [5]. Very recently, we developed a new method to prepare hollow copper microspheres, which used ZSM-5 molecular sieve as a template [8]. The ZSM-5 molecular sieve has the merits of ease of removal and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the modification of UPD Ag can significantly reduce the thermal destruction of SERS-active substrates. A new type of micrometer-sized hollow copper sphere was reported by Xia et al [16] The process involves using ZSM-5 molecular sieve as a template such that at various stages of pretreatment the core material can be omitted because of the inherent nature of the ZSM-5 molecular sieve. Alexander et al [17] presented a high-throughput method for fabricating large arrays of SERS-active gold dimers.…”
Section: Sers Substratesmentioning
confidence: 99%
“…Wermelinger and Spolenak [194] investigated the microstructure changes upon indentation of single-crystalline (100)-oriented silicon by transmission electron microscopy and Raman microscopy. Thermo-Raman spectroscopy was used by Frost et al [195] to characterize selected layered double hydroxides of formula Cu 6 Al 2 (OH) 16 CO 3 and Zn 6 Al 2 (OH) 16 CO 3 . Kumar et al [196] characterized the structure of the lead-free relaxor Ba(Ti 0.70 Sn 0.30 )O 3 using micro-Raman spectroscopy from 80 to 500 K, which indicated three local phase sequences.…”
Section: Other Crystalline Materialsmentioning
confidence: 99%
“…In addition, the use of non volatile surfactants can be avoided, which may be adsorbed onto the synthesized pyrrole-platinum poly (PPy-Pt) complex spheres and interfere with their possible applications in catalysis. Very recently, we developed a new method for preparation of silver core-shell materials and hollow materials by using 5A and ZSM 5 molecular sieves as templates [14,15]. To the best of our knowledge, there have been few reports on preparation of hollow conductive PPy spheres based on surface modified molecular sieves.…”
mentioning
confidence: 99%